Can social media visibility affect institutional ownership and trading consensus on sharia stocks? - Ahmad Hafiyyan Shibghatalloh; Sugeng Wahyudi; Noni Setyorini; Abdulhamid Ali Abukil (Journal of Islamic Accounting and Finance Research, 2023)
Purpose - This study aims to examine the effect of Instagram users’ responses to corporate Instagram post (Likes and Comments) toward trading consensus and institutional ownership of sharia stocks in Indonesia.Method - This study used purposive sampling technique. The number of samples in this study were 158 companies registered in ISSI (Indonesia Sharia Stock Index) and having an active Instagram account. Data processing using SPSS.26 with Ordinary Least Square (OLS).Result - The results showed that Instagram users’ responses increased the institutional investor and individual investor in sharia stock. The interpretation for this findings that such Instagram activities increase the visibility of the company across a more diverse group of investors. This increase visibility makes information more accessible to individual and institutional investors, so that they are attracted to invest more in sharia stock.Implication - Sharia issuer companies should also use social media to provide valid information to potential investors. So that it can be one of the foundations of investors in choosing Islamic stocks.Originality - This research is the first study that used social media to measure sharia stock ownership.